Perbedaan Tingkat Kecemasan Primigravida dan Multigravida Trimester III dalam Menghadapi Persalinan - Theresia Limbong; Dian Pratiwi Halman; Syaniah Umar (Jurnal Ilmiah Kesehatan Sandi Husada, 2022)
Introduction: Pregnancy is one of the expressions of self-embodiment as a future mother and father. Pregnant women experience anxiety about various problems from one trimester to the next. Anxiety changes as the pregnancy get older. Objective: To know the difference in anxiety between primigravida and multigravida pregnant women in iii trimester pregnancy. Method: This study used a cross-sectional approach using a consecutive sampling technique. Data was collected by filling out the respondent's characteristic questionnaire and the HRS-A questionnaire. Results: Chi-square test age 0.426; education 0.567; jobs 0.224; and income 0.132; while the multigravida group consisted of ages 0.620; education 0.582; jobs 0.594; and income 0.05. Conclusion: That age, education, occupation, and income do not affect the difference in the anxiety level of pregnant women; there is a significant difference in the anxiety level of primigravida pregnant women and multigravida III trimesters.